2019
DOI: 10.1021/acsabm.9b00303
|View full text |Cite
|
Sign up to set email alerts
|

Voltaglue Electroceutical Adhesive Patches for Localized Voltage Stimulation

Abstract: Electroceuticals have been proposed as nerve-and tissue-stimulating therapeutics for diverse ailments such as fracture repair, Parkinson's disease, diabetes, hypertension, and wound healing. However, academic and clinical investigation of electroceutical hypotheses remains intangible due to lack of suitable interfaces required for the application of uniform electric fields to localized tissues. There is an unmet need to develop materials that match the mechanical properties of soft tissues, are electrically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 58 publications
(133 reference statements)
0
33
0
Order By: Relevance
“…Synthesis and structure-property relationships of voltage, current, electrode design, DC/AC signals, cation, and temperature on viscoelastic properties have been previously reported. [22,26,28,[30][31][32] Electric fields are hypothesized to reduce diazirine to a reversible and semi-stable diazirinyl radical (t 1 = 2 = 46 s), that then transitions to a shortlived (6 ns) carbene intermediate. [22,26] The primary evidence supporting this mechanism is diazirine decay, nitrogen gas emission, and rheological viscoelastic transition from viscous to elastic stress deformation (aka gelation) of the high solute (� 50 %) PAMAM-diazirine formulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis and structure-property relationships of voltage, current, electrode design, DC/AC signals, cation, and temperature on viscoelastic properties have been previously reported. [22,26,28,[30][31][32] Electric fields are hypothesized to reduce diazirine to a reversible and semi-stable diazirinyl radical (t 1 = 2 = 46 s), that then transitions to a shortlived (6 ns) carbene intermediate. [22,26] The primary evidence supporting this mechanism is diazirine decay, nitrogen gas emission, and rheological viscoelastic transition from viscous to elastic stress deformation (aka gelation) of the high solute (� 50 %) PAMAM-diazirine formulations.…”
Section: Resultsmentioning
confidence: 99%
“…Voltaglue (VG) consists of a polyamidoamine (PAMAM) dendrimer (generation 5, G5) grafted with diazirine molecules on the surface of the dendrimer. Synthesis and structure‐property relationships of voltage, current, electrode design, DC/AC signals, cation, and temperature on viscoelastic properties have been previously reported [22,26,28,30–32] . Electric fields are hypothesized to reduce diazirine to a reversible and semi‐stable diazirinyl radical (t 1/2 =46 s), that then transitions to a short‐lived (6 ns) carbene intermediate [22,26] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Crosslinking in Voltaglue can be initiated with diverse electrode geometries such as disposable three‐electrode chips, [ 1,2 ] bioresorbable interdigitated 3D‐graphene electrodes (IDE), [ 3 ] and semiconductive substrates. [ 4 ] Despite these advances, Voltaglue has some limitations (when stimulated/electrocured) in aqueous environments: 1) it displays low storage modulus (1 kPa) in comparison to photo‐ and thermal‐curing (100 kPa) and 2) the water electrolysis that takes place at –1.3 V may lead to excessive foaming. Recently, we reported that most of these disadvantages could be overcome by employing donor–acceptor‐based electrocuring in organic environments.…”
Section: Figurementioning
confidence: 99%
“…Blended formulations may be further optimized with higher voltages or alternating current for faster activation. [ 4,15 ]…”
Section: Figurementioning
confidence: 99%